(1-x)+3x=-2(x+1)

Simple and best practice solution for (1-x)+3x=-2(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1-x)+3x=-2(x+1) equation:


Simplifying
(1 + -1x) + 3x = -2(x + 1)

Remove parenthesis around (1 + -1x)
1 + -1x + 3x = -2(x + 1)

Combine like terms: -1x + 3x = 2x
1 + 2x = -2(x + 1)

Reorder the terms:
1 + 2x = -2(1 + x)
1 + 2x = (1 * -2 + x * -2)
1 + 2x = (-2 + -2x)

Solving
1 + 2x = -2 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
1 + 2x + 2x = -2 + -2x + 2x

Combine like terms: 2x + 2x = 4x
1 + 4x = -2 + -2x + 2x

Combine like terms: -2x + 2x = 0
1 + 4x = -2 + 0
1 + 4x = -2

Add '-1' to each side of the equation.
1 + -1 + 4x = -2 + -1

Combine like terms: 1 + -1 = 0
0 + 4x = -2 + -1
4x = -2 + -1

Combine like terms: -2 + -1 = -3
4x = -3

Divide each side by '4'.
x = -0.75

Simplifying
x = -0.75

See similar equations:

| 5x-20+2x+53=180 | | -4z-1=12 | | x+5/x+4=7 | | (-8b)-(-12b)+2=(-10) | | 5x-20+2x-53=180 | | 7b-14= | | 14m-3=12m-15 | | 7t-5t-1=3 | | 2(w+2)=10 | | Y-3=8(x-2) | | 2990=4x+6y | | 3x(8+2)= | | 5p-(-20)-(-11)=(-14) | | 3y+12=27-2y | | 8x^2+36x-288=0 | | (-17j)-2j=(-19) | | 7x^2+2x=3600 | | 32=6p-4 | | 2(u+2)=20 | | 5k-2(k-5)=17 | | X-45=100 | | 14-d=(-4) | | 4(2k-1)=3(K+2) | | (-11j)-(-8j)=(-9) | | 2(15x-7+1.5x+87.5)=p | | 3(n+7)-2(n-1)=18 | | 2x^2+9x=72 | | B=85+(20+8)w | | -14-14-18= | | =750 | | g-4.4=1.125 | | a^2-10a-20=5 |

Equations solver categories